The development of a school readiness screening instrument for grade 00 (pre-grade R) learners - Mohamed, Shireen Ahmed (University of the Free State, 2013)
School readiness is increasingly being recognised as major need in education as it has far reaching consequences in a child’s educational and later life. Inadequate preparation and lack of timeous identification of at risk factors in this phase of life has many negative sequaleae. The literature has highlighted the role of prediction variables for scholastic achievement to facilitate appropriate intervention. School readiness assessments have been criticised for a lack of multidimensional assessment approach. In contrast to previous studies, which are generally univariate in their approach, this research aimed at a multidimensional approach to assessing at risk factors in grade 00 learners in the age cohort (4-5 ½ years). A further aim was to investigate the predictor variables/isolate the dimensions of development that would be linked to academic achievement in reading, spelling and maths in grade 1. The behaviours underpinning eight developmental domains and 19 dimensions (indicated in brackets) namely, 1) Cognitive (Ability, Approaches to learning); 2) Perceptual (Body awareness, Auditory, Spatial ability); 3) Speech (Speech, Language); 4) Neurological (Fine motor, Gross motor, Low tone), 5) Emotional (Empathy, Emotional Regulation, Self-confidence); 6) Social (Interpersonal competencies, Social regulation behaviour, Social graces, Play); 7) Developmental (Concentration, Sensory) and 8) Independence were identified in the form of a screening instrument (comprehensive version) for assessment of grade 00 learners. Factor analyses reduced the total pool of 214 items to 100 on the Comprehensive version of the test. A shortened version of the screening instrument was also compiled, using 42 items. Cronbach α coefficient’s yielded high values (>0.7) indicating sound reliabilities for the 19 dimensions and 8 domains. A convenience sample of 579 grade 00 learners in Durban schools were evaluated on the questionnaire by their teachers and parents in the first phase of the study. The same cohort were followed up in grade 1 and assessed on South African standardised tests, the ESSI and VASSI in spelling, reading and maths. The results indicated that the domains of Cognitive, Perceptual, Speech and Language displayed acceptable validity to predict academic achievement of grade 1 learners. The remaining domains, viewed as indirect variables, play an integral part in the child’s future scholastic achievement. Results of a stepwise regression analyses showed that the combined value of four predictor variables (Cognitive Ability, Social Regulation, Sensory, and Speech) roughly contribute to 17% of the variance in academic achievement of Grade 1 learners. As MANOVA analyses showed small effect sizes between the mean domain and dimension scores for the two gender groups, norms were calculated for the entire sample in the form of percentiles and stanines. The present research supports previous studies that show that early cognitive, perceptual and speech and language are strong predictors of grade 1 academic achievement. The findings of the study have implications at policy and practice level for early identification and intervention. It is suggested that the screening instrument be used to facilitate curriculum goals at preschool level, that the predictor variables be targeted for intensive intervention at preschool level and later schooling to ensure positive academic trajectories.

Skoolgereedheid word al hoe meer erken as ‘n belangrike faktor in die opvoedkunde aangesien dit verrykende gevolge in ‘n kind se opvoedkundige en latere lewe het. Onvoldoende voorbereiding en ‘n gebrek aan vroeë identifisering van risiko faktore in hierdie lewensfase het negatiewe skolastiese gevolge. Die literatuur beklemtoon die rol van veranderlikes wat skolastiese prestasie kan voorspel sodat toepaslike intervensies gefasiliteer kan word. Die assessering van skoolgereedheid is in die verlede weens ‘n gebrek aan ‘n multi-dimensionele benadering, gekritiseer. In teenstelling met vorige studies, wat gewoonlik ‘n enkelvoudige benadering gevolg het, is met hierdie navorsing ‘n multi-dimensionele benadering gevolg, ten einde die risiko faktore vir graad 00-leerders, in die 4-5 ½ ouderdomsgroep, vas te stel. ‘n Verdere doel was om die veranderlikes/dimensies van ontwikkeling wat graad 1-leerders se akademiese prestasie in lees, spelling en wiskunde kan voorspel, te identifiseer. Gedragskomponente op agt ontwikkelingsdomeine en 19 dimensies (aangedui in hakies), naamlik 1) Kognitief (vermoë, benadering tot leer), 2) Perseptueel (liggaamsbewustheid, ouditief, ruimtelike vermoë); 3) Spraak (spraak, taal); 4) Neurologies (fyn motories, groot motories, lae tonus); 5) Emosioneel (empatie, emosionele regulasie, selfvertroue); 6) Sosiaal (interpersoonlike bevoegdhede, sosiale regulerende gedrag, sosiale vaardighede, spel); 7) Ontwikkeling (konsentrasie, sensories) en 8) Onafhanklikheid is geïdentifiseer en in ‘n siftingsvraelys (omvattende weergawe) saamgevoeg vir die evaluering van graad 00-leerders. Faktorontledings is benut ten einde die aanvanklike aantal items van 214 na 100 te verminder vir die omvattende weergawe van die siftingsinstrument. ‘n Verkorte weergawe van die siftingsinstrument is ook opgestel wat slegs uit 42 items bestaan. Cronbrach α-koëffisiënte vir die 19 dimensies en agt domeine toon aan dat aanvaarbare interne konsekwente metings (>0.7) voorkom. Tydens die aanvanklike fase van die studie is met behulp van ‘n beskikbaarheidsteekproef 579 graad 00-leerders, verbonde aan skole in die Durban omgewing, betrek. Hierdie leerders is deur hul onderwysers en ouers op die vraelyste geëvalueer. Dieselfde groep leerders is in graad 1 opgevolg en met behulp van Suid-Afrikaans gestandardiseerde toetse, naamlik die ESSI-Lees en speltoets en die VASSI wiskundetoets, geëvalueer. Die resultate het aangetoon dat die kognitiewe, perseptuele, spraak en taal domeine aanvaarbare geldigheid toon deurdat dit daarin slaag om die graad 1-leerders se akademiese prestasie te voorspel. Die ander domeine speel ‘n belangrike rol in die leerder se toekomstige skolastiese prestasie. Die resultate van ‘n stapsgewyse regressie-ontleding toon aan dat vier veranderlikes (kognitiewe vermoë, sosiale regulering, sensories en spraak) ongeveer 17% van die varianse in graad 1-leerders se akademiese prestasie verklaar. Aangesien die MANOVA-resultate klein effekgroottes vir die twee geslagte rakende die gemiddelde domein- en dimensietellings aangedui het, is norms vir die groep as geheel in terme van persentiele en staneges, bereken. Die navorsingbevindinge van hierdie studie ondersteun die bevindinge van vorige studies, naamlik dat kognitiewe, perseptuele, spraak en taal veranderlikes belangrike voorspellers van van graad 1 akademiese prestasie is. Die bevindings van die studie het op beleids- en praktiese vlak belangrike implikasies vir die identifisering van skoolgereedheid en vir moontlike intervensies. Daar word aanbeveel dat die siftingsinstrument gebruik word om kurrikulumdoelwitte op voorskoolse vlak te fasiliteer en dat die voorspellingsveranderlikes gebruik word vir ingryping op voorskoolse vlak om akademiese prestasie te verbeter.
Thesis (Ph.D. (Child Psychology))--University of the Free State, 2013
Keywords: Readiness for school -- Testing; School age (Entrance age); Holistic development; Grade 1; Predictor variables; Multidimensional developmental assessment; Pre K; School readiness; Grade 00